The therapeutic potential of irisin to mitigate the risk of metabolic syndrome in postmenopausal women - Parkin, Rebecca A.; Murray, Andrew J. (Frontiers in Reproductive Health, 2024)
Oestradiol withdrawal at menopause predisposes women to metabolic syndrome, a cluster of interrelated conditions including obesity, insulin resistance, dyslipidaemia and hypertension that together confer an increased risk of developing type 2 diabetes mellitus and cardiovascular disease. Hormone replacement therapies are commonly used to treat acute symptoms of the perimenopausal period, and whilst they have been associated with metabolic improvements in many studies, longterm use is considered unviable. Novel approaches are required to mitigate the risk of postmenopausal metabolic syndrome. In 2012, the exercise-inducible myokine irisin was isolated from the skeletal muscle of mice and identified to have anti-obesity and antidiabetic effects in vivo.Irisin is now recognised to exert pleiotropic action on cognitive, bone and metabolic health. There is accumulating evidence from in vitro and in vivo rodent studies that irisin can mitigate each component condition of metabolic syndrome. In postmenopausal women, independent associations have been observed between a) exercise and plasma irisin concentration and b) plasma irisin concentration and reduced incidence of metabolic syndrome. To date, however, no study has considered the mechanistic basis by which irisin, whether exercise-induced or exogenously administered, could reduce the incidence or severity of metabolic syndrome in postmenopausal women. This review aims to analyse the literature concerning the metabolic actions of irisin, with a focus on its therapeutic potential for metabolic syndrome driven by a state of oestradiol depletion. It evaluates the practicality of exercise as a therapy and discusses other irisin-based therapeutic strategies that may alleviate postmenopausal metabolic syndrome. Finally, it highlights areas where future research is required to advance knowledge of irisin's biological action such that it could be considered a viable candidate for clinical application.